2020
DOI: 10.1038/s41598-020-78928-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association studies in tropical maize germplasm reveal novel and known genomic regions for resistance to Northern corn leaf blight

Abstract: Northern Corn Leaf Blight (NCLB) caused by Setosphaeria turcica, is one of the most important diseases of maize world-wide, and one of the major reasons behind yield losses in maize crop in Asia. In the present investigation, a high-resolution genome wide association study (GWAS) was conducted for NCLB resistance in three association mapping panels, predominantly consisting of tropical lines adapted to different agro-ecologies. These panels were phenotyped for disease severity across three locations with high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 86 publications
(105 reference statements)
0
17
0
Order By: Relevance
“…The BTx623 × SC155 QTL on chromosome one colocalized with the ortholog of a translation initiation factor IF‐2 (Poland et al., 2011). The BTx623 × SC155 QTL on chromosome two overlapped with six previously identified candidate genes, including genes with a leucine‐rich repeat domain and a basic‐leucine zipper domain (Poland et al., 2011; Rashid et al., 2020), a gene encoding a BTB/POZ (Poland et al., 2011), a gene with an EXPERA domain (Ding et al., 2015), a SANT‐associated gene (Rashid et al., 2020), and a glutathione S‐transferase encoding gene (Wisser et al., 2011). There was no overlap with QTL for anthracnose or target leaf spot reported in previous studies using the BTx623 × SC155 mapping population (Kimball et al., 2019; Patil et al., 2017).…”
Section: Resultsmentioning
confidence: 82%
“…The BTx623 × SC155 QTL on chromosome one colocalized with the ortholog of a translation initiation factor IF‐2 (Poland et al., 2011). The BTx623 × SC155 QTL on chromosome two overlapped with six previously identified candidate genes, including genes with a leucine‐rich repeat domain and a basic‐leucine zipper domain (Poland et al., 2011; Rashid et al., 2020), a gene encoding a BTB/POZ (Poland et al., 2011), a gene with an EXPERA domain (Ding et al., 2015), a SANT‐associated gene (Rashid et al., 2020), and a glutathione S‐transferase encoding gene (Wisser et al., 2011). There was no overlap with QTL for anthracnose or target leaf spot reported in previous studies using the BTx623 × SC155 mapping population (Kimball et al., 2019; Patil et al., 2017).…”
Section: Resultsmentioning
confidence: 82%
“…A GWAS was conducted using a mapping panel that included tropical/subtropical inbred lines from CIMMYT breeding programs in Asia, Mexico, Kenya, Zimbabwe, and Colombia that are also acclimatized to the Asian tropics. The CAAM panel was previously used to study traits like resistance to sorghum downy mildew (Rashid et al, 2018), northern leaf corn blight (Rashid et al, 2020), and root traits under drought conditions (Zaidi et al, 2016) in Asian environments. Phenotypic evaluation of CAAM panel for charcoal rot at Hyderabad and Ludhiana, revealed that the panel was skewed toward susceptibility, possibly because both these locations had ideal environment for pathogen infection and spread, and the artificial inoculation using the toothpick method reduced the chances of escapes.…”
Section: Discussionmentioning
confidence: 99%
“…of non-missing markers, where IBS1 and IBS2 are the states in which the two inbred lines share one or two alleles at a marker (Bishop and Williamson, 1990). Linkage disequilibrium (LD) was estimated on adjacent pairwise r 2 -values between adjacent SNPs among the SNPs from the GBS data and physical distances between those SNPs as described in Rashid et al (2020). Manhattan and quantilequantile plots were created using the association results.…”
Section: Gwas and Haplotype Regressionmentioning
confidence: 99%
“…Right now, GWAS have been widely used to detect the genomic regions correlated with the complex traits in human, animals, and plants. In plants, GWAS have been detected many genes associated to the complex traits, such as in Arabidopsis, rice, maize, sorghum, wheat, barley, and many other plants [2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Phenotypic data and genome-wide genotypes are required in GWAS.…”
Section: Introductionmentioning
confidence: 99%